Investigation of the perceptual and cognitive asymmetry in the auditory system in patients with adolescent idiopathic scoliosis - Burçin Akçay; Gonca İnanç; Ata Elvan; Metin Selmani; Mehmet A. Cakiroglu; Ömer Akcali; İsmail S. Satoglu; Adile Oniz; İbrahim E. Simsek; Murat Ozgoren (AOSIS, 2021)
Background: Studies have shown that perceptual and cognitive asymmetries are present in the auditory system in patients with adolescent idiopathic scoliosis (AIS). The Dichotic Listening (DL) paradigm was formerly performed in non-forced (NF) conditions only, and no study has examined the conditions of attention to one ear. Objective: To investigate the perceptual and cognitive asymmetry in the auditory system in patients with AIS as well as the asymmetry changes according to the curvature characteristics of patients with AIS. Method: The DL paradigm was performed on 38 patients with AIS and 10 healthy individuals in all conditions (NF, Forced Right [FR], Forced Left [FL]). Results: In the NF and FL conditions, the mean number of correct responses for the left ear was significantly lower in patients with AIS than in healthy individuals (p 0.05). The correct responses for the right ear in the NF condition, right and left ear in the FR condition, and right ear in the FL condition did not show a significant difference between the groups (p 0.05). Also, there was no difference between patients with AIS with both functional 3-curve and 4-curve (p 0.05). Conclusion: Our study indicates perceptual and cognitive asymmetry or lateralisation in the auditory system in patients with AIS. The asymmetry might be caused by the inability to direct their attention to the left ear, which is not affected by their curvature type. Further studies are needed to investigate perceptual and cognitive asymmetry behaviour models in the auditory system in patients with AIS. Clinical implications: Determination of perceptual and cognitive asymmetry in the auditory system may offer a new perspective on conservative treatment protocols for AIS patients. Besides, the DL paradigm can be easily used in patients with AIS as a non-invasive evaluation method in clinics.